Bacillus thuringiensis and Chlorantraniliprole Trigger the Expression of Detoxification-Related Genes in the Larval Midgut of Plutella xylostella - Shabbir, Muhammad Zeeshan; Yang, Xiangbing; Batool, Raufa; Yin, Fei; Kendra, Paul E.; Li, Zhen-Yu (Frontiers in Physiology, 2021)
BACKGROUND: Diamondback moth (DBM), Plutella xylostella (L.) has developed resistance to many insecticides. The molecular mechanism of DBM resistance to Bt combined with chlorantraniliprole remains undefined. In this study, a field-original-resistant strain (FOH-DBM) was selected with Bacillus thuringiensis toxin (Bt-G033A), chlorantraniliprole (CL), and a mixture of Bt + chlorantraniliprole (Bt + CL) to evaluate the resistance level. Additionally, transcriptomic profiles of a susceptible (SS-DBM), field original resistant (FOH-DBM), Bt-resistant (Bt-DBM), chlorantraniliprole-resistant (CL-DBM), and Bt + chlorantraniliprole-resistant (BtC-DBM) strains were performed by comparative analysis to identify genes responsible for detoxification. RESULTS: The Bt-G033A was the most toxic chemical to all DBM strains among the three insecticides. The comparative analysis identified 25518 differentially expressed genes (DEGs) between pairs/combinations of five strains. DEGs were enriched in pathways related to metabolic and catalytic activity and ABC transporter in resistant strains. In total, 17 metabolic resistance-related candidate genes were identified in resistance to Bt-G033A, CL and Bt + CL by Co-expression network analysis. Within candidate genes, the majority was up-regulated in key genes, including cytochrome P450, glutathione S-transferase (GST), carboxyl-esterase and acetyl-cholinesterase in CL and BtC resistant strains. Furthermore, aminopeptidase (APN), alkaline phosphatase (ALP), cadherin, trypsin, and ABC transporter genes were eminent as Bt-candidate genes. Expression patterns of key genes by qRT-PCR confirmed an association in the detoxification process. CONSLUSIONS: To date, the present study is the most comprehensive research presenting functional transcriptome analysis of DBM using Bt toxin and chlorantraniliprole combined insecticidal activity.